Deriving Trajectory Tracking Requirements for a Small Size League Robot - Farias, Gabriel B.; Maximo, Marcos R. O. A.; Afonso, Rubens J. M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
In the development of an engineering project, it is common to face many design choices in order to achieve a final solution. The earlier such choices are made, the greater the influence in the design and the more impactful it is to change the decision later. Therefore, these decisions must be accompanied by a thorough analysis to assure that the solution is adequate to the project. In this paper, we contribute with a method to obtain design requirements using a Monte Carlo approach in the context of the design of a team for the RoboCup Small Size League competition. Focusing in the task of following trajectories, we analyze the impact of parameters that drive the robot design, the feedback control information, and the auxiliary computer software.